(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article analyzes the current features of taxation of e-commerce within the Eurasian Economic Union, with a particular focus on the experience and challenges faced by the Kyrgyz Republic. It examines the legal aspects of taxation of digital services and cross-border trade, provides statistics on revenue collection, and highlights the main obstacles to developing an effective tax policy under conditions of integration. Special attention is given to the prospects for harmonizing fiscal regulation and digitalizing tax administration across the EAEU.